2018
DOI: 10.1111/evo.13497
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide regulatory deterioration impedes adaptive responses to stress in inbred populations ofDrosophila melanogaster*

Abstract: Inbreeding depression is often intensified under environmental stress (i.e., inbreeding-stress interaction). Although the fitness consequences of this phenomenon are well-described, underlying mechanisms such as an increased expression of deleterious alleles under stress, or a lower capacity for adaptive responses to stress with inbreeding, have rarely been investigated. We investigated a fitness component (egg-to-adult viability) and gene-expression patterns using RNA-seq analyses in noninbred control lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
3
0
2
Order By: Relevance
“…In addition, the trait analyzed by Ayroles et al . (2009) was the amount of gene expression, and it has been shown that there is not a clear relationship between differential gene expression due to inbreeding and inbreeding depression (Schou et al ., 2018), so the mode of gene action analyzed by Ayroles et al . (2009) might not be related at all with inbreeding depression for fitness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the trait analyzed by Ayroles et al . (2009) was the amount of gene expression, and it has been shown that there is not a clear relationship between differential gene expression due to inbreeding and inbreeding depression (Schou et al ., 2018), so the mode of gene action analyzed by Ayroles et al . (2009) might not be related at all with inbreeding depression for fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, as acknowledged by Ayroles et al (2009), the proportion of putative overdominant loci could also be ascribed to pseudooverdominance generated by linked deleterious mutations (see Schou et al, 2017;Waller, 2021), a likely explanation considering the reduced genetic length of the Drosophila genome and its multiple inversions. In addition, the trait analyzed by Ayroles et al (2009) was the amount of gene expression, and it has been shown that there is not a clear relationship between differential gene expression due to inbreeding and inbreeding depression (Schou et al, 2018), so the mode of gene action analyzed by Ayroles et al (2009) might not be related at all with inbreeding depression for fitness. In a large meta-analysis of estimates of selection coefficients in natural populations carried out by Thurman & Barrett (2016), 3416 estimates were ascribed to directional selection and only 70 to heterozygote advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Відомо, що інбредна депресія може бути слабко виражена у сприятливих умовах та значно інтенсифікується в умовах стресу, що свідчить про зниження здатності інбредів до виживання в умовах, що змінюються [4]; у нашій роботі зниження стрес-стійкості було показано лише для інбредної лінії ri(Оз).…”
Section: результати та обговоренняunclassified
“…Механізм зниження пристосованості за інбредної депресії пов'язаний із підвищенням рівня гомозиготності за алелями, які негативно впливають на життєздатність, та, меншою мірою, з підвищенням гомозиготизації у тих локусах, які у гетерозиготному стані зумовлюють зростання виживаності (шляхом «наддомінування») [1; 2]. Прискоренню інбредної депресії сприяють епістатичні взаємодії між генами, які негативно впливають на життєздатність [3], а також стресові умови: інбредні особини характеризуються зниженою здатністю адаптуватися до стресу шляхом регуляції генної активності (у порівнянні з організмами з вищим ступенем гетерозиготності) [4]. Між тим, у літературі описано багато прикладів того, коли інбридинг не призводив до негативних наслідків [5].…”
unclassified
“…In this issue, Schou et al (2018) explore these two major hypotheses empirically. The authors applied temperature stress (23°C control; 31°C stress) to inbred and control lines of Drosophila melanogaster eggs, larvae, and adults and measured * This article corresponds to Schou, M. F., J. Bechsgaard, J. Muñoz, and T. N. Kristensen.…”
mentioning
confidence: 99%